To Assess the Quality of Life among Primary Caregivers of Intellectually Disabled Children Attending Outpatient Department in a Tertiary Health Center of City - Khare, Sumit; Parkhe, Shilpa; Parkhe, Shilpa; Gunjal, Pratibha; Shinde, Sonali; Arbatti, Rama (International Journal of Nursing Research, 2023)
Introduction: Acceptance of child with intellectual disability (ID), once called mental retardation, becomes difficult to parents and the whole family, particularly when competence and achievement are very much valued in modern world. A parent shows a series of reaction including shock, denial, guilt, sorrow, rejection, and acceptance after knowing that their child is disabled. It is also important to note that caring for a child with disability does not equally affect all parents. There are families who cope well despite the adversity. There could be a number of factors that can affect the quality of life (QOL) of carers which could include severity of the disability of the child, presence of cognitive or behavioral problems, socioeconomic status of the families, lack of education, low social support, etc. The research investigated differences of overall QOL between QOL for caregivers of children with autism spectrum disorder and an ID was compared to QOL for those caring for a normally developing child. Materials and Methods: The study was conducted in Maharashtra Institute of Mental Health, Sassoon General Hospital, Pune. Target population was primary caregivers of intellectually disabled children. The samples were selected by convenience sampling technique, a total of 100 samples were selected. Results: Data analysis was done by descriptive and inferential statistics. Chi-square test was applied to find out the association between the study findings with selected demographic variables. The Chi-square value for the type of family was 24.6 with 0.05% level of significance, which is greater than tabulated value; hence, there was a significant association between the type of family and QOL of primary caregivers. This was also evident that the overall QOL of primary caregivers comes under satisfactory category. Conclusion: The study concludes that the QOL of primary caregivers is related to the type of disability, duration of disability, and the social support available for the caregivers. More the duration, more the social support, and lesser disability lead to better QOL of primary caregivers of intellectually disabled children.